MANAGEMENT OF TECHNOLOGY TRANSFER IN A REGION. BASIC PREMISES - Dalmau Porta, Juan Ignacio; Pérez Castaño, Bernardo Javier; Baixauli Baixauli, Joan Josep (Cuadernos de Administración, 2007)
In this paper we analyze the foundations of a model for managing the technology transfer in a region, focused on the impaet in development and the strategic objeetives of the region, the produetive system and the seientifie technologieal system. Increasingly arises the special care that regions, Countries, companies and organizations should have on the components that leverage and support towards future competitiveness and development, increasing interest in proposing and implementing models to find new management approaches, characterized by the strategic role that is granted to the intangible, value creatíon, allianees and the building of social capital. In addition, to create value, to acrueve and maintain competítíve advantages, we must combine simultaneously: Significant increases in productivity, production of innovation and flexibility. The paper develops concepts related to Drivers of competitiveness and development. technology transfer and relations between enterprises and research units; Models of relationships between research units. enterprises, govenunent (Sabato Triangle. Triple Helix model, New Way of Knowledge Production). Finally, present the foundation of the model based on tbe conformation ofthe GUIES system (Govemment - Research Units - Enterprises - Society)